Utilization of Single Phase Pure Sine Wave Inverters in Electrical Energy Conversion Systems for Solar Panels with Variable Loads - Yudi Wijanarko; Ekawati Prihatini; Selamat Muslimin; Nyayu Latifah Husni; Muhammad Khoirun Nadir (Politeknik Negeri Jakarta, 2024)
The inverter built in this research is used to convert direct current into alternating current with a size of 3000 watts, which has a DC input voltage of 24 volts. This inverter has a large capacity and can generate enough electricity to run different huge electrical devices or several units at once. It's made utilizing energy-efficient technology to cut down on energy waste during conversion. Furthermore, safeguards such voltage surge and overcurrent prevention guarantee the operational safety of the inverter. The inverter was built using the PWM method and variable loads (resistive load, inductive load and capacitive load), with the aim of evaluating the inverter's ability to handle resistive, inductive and capacitive loads and to see how the inverter responds to load changes dynamically. Based on observations and calculations, higher loads are positively correlated with higher inverter power and efficiency. The inverter has a max output of 664.62 watts and 229 Volt is the output voltage attained. This demonstrates that the EGS002 PSW inverter produces AC voltage of high quality with precise and steady characteristics.